Pore Characteristics of Lacustrine Shale Oil Reservoir in the Cretaceous Qingshankou Formation of the Songliao Basin, NE China - Xiaomeng Cao; Yuan Gao; Jingwei Cui; Shuangbiao Han; Lei Kang; Sha Song; Chengshan Wang (Energies, 2020)
Shale oil is hosted in nanopores of organic-rich shales, so pore characteristics are significant for shale oil accumulation. Here we analyzed pore characteristics of 39 lacustrine shale samples of the Late Cretaceous Qingshankou Formation (K2qn) in the Songliao Basin, which is one of the main shale oil resource basins in China, using field emission-scanning electron microscopy (FE-SEM), and low-pressure nitrogen adsorption. We accomplished fractal analysis, correlation analysis using correlation matrix and multidimensional scaling (MDS), and prediction of fractal dimensions, which is the first time to predict pore fractal dimensions of shales. Interparticle pores are highly developed in K2qn. These shales have mesoporous nature and slit-shaped pores. Compared with the second and third members (K2qn2,3), the first member of the Qingshankou Formation (K2qn1) has a larger average pore diameter, much smaller surface area, fewer micropores, simpler pore structure and surface indicated by smaller fractal dimensions. In terms of pore characteristics, K2qn1 is better than K2qn2,3 as a shale oil reservoir. When compared with marine Bakken Formation shales, lacustrine shales of the Qingshankou Formation have similar complexity of pore structure, but much rougher pore surface. This research can lead to an improved understanding of the pore system of lacustrine shales.